The values ​​and principles of the Iraqi artist between reality and ambition (Journal of the College of Basic Education, 2022)
Since the Iraqi fine art movement began. At the end of the forties of the last century, different forms were inspired by nature or inspired by the artist's imagination in building an Arab plastic painting that has its own specificity or its various design creations. As a unique aid in the modernity of the Arab and Iraqi formation in particular. In parallel with the pioneers of plastic arts and the Iraqi design movement, and in the development of the first attempts and exit from the classic form, and in an attempt to root an experience that fits the spirit of modernity and continuous creativity between art and plasticity, it is governed by the inevitability of that civilizational conflict between the old and the renewal.